New grain discharge terminal at Santos Port, Brazil - Bergerman, Mauro (Kansas State University, 2012)
The thesis assesses the viability of investing in a new grain discharge terminal at the port of Santos, located in the Brazilian southern region, used mostly for wheat but also for malt and malting barley operations. ABC Intl suffered losses of more than USD 1.0 million in 2006 due to demurrage costs at berth 39, used by ABC Intl to export and import grains, sugar and soybean. Congestion tends to increase with the growth of Brazilian soybean and sugar cane production and exports (average 5.0% per year) and 2.0% growth of wheat imports. Demurrage losses are expected to amount to USD 3.0 million by the year 2011 if no investments are made. A brief summary of Brazilian wheat supply and demand for the last five years is presented. Brazil is a net importer between 6.0 and 8.0 million metric tons of wheat per year, to supply the 10.0 million metric ton internal demand. Brazilian wheat imports through the port of Santos average 1.6 million metric tons per year from 2000 to 2006. Sao Paulo is the most populated Brazilian city with more than 18.0 million inhabitants. Its wheat consumption amounts to a third of the total Brazilian consumption and represents around 3.0 million metric tons per year. The thesis analyzes data related to berth 39 activities in the past seven years. A 56-day lineup in 2006 represented more than USD 1.0 million demurrage costs. The thesis forecasts the activity of berth 39 for next five years with and without investment at the new terminal. The new terminal will result in an average of USD 1.8 million savings on demurrage costs over five years. Codesp, Companhia Docas de Sao Paulo, the governmental authority in the port of Santos, is offering a unique opportunity for ABC Intl to invest in a new terminal for grain imports granting the land at no cost. The new terminal would be located at the middle of the port (berth 13/14) close to the railroad and the main avenue in the port of Santos, allowing discharging, storing and loading grain to trucks and wagons. ABC Intl needs to invest USD 5.0 million in the new terminal. It comprises the dismantling and rebuilding of all the grain discharge equipment that will be moved from shed 39 to the new terminal, including two suckers and conveyor belts. The thesis analyzes four different wheat import scenarios for the next five years. In addition, the same scenarios are analyzed for a 10-year period for comparison purposes. The weighted average of the Net Present Value of the four different investment scenarios, considering the probability of each occurring, is a positive USD 78,908 with 13.1% Internal Rate of Return, compared to 9.0 % ABC Intl opportunity cost of capital. It must be considered that the Net Present Value is a conservative figure since it does not take into account the savings on demurrage at berth 39, forecasted to be more than USD 3.0 million in the year 2011 if the company does not invest in the new terminal construction. It is recommended the ABC Intl invest in the new terminal to improve the overall logistics of the port and the quality of the service. This will avoid unnecessary demurrage costs and improving shareholders wealth by investing in a project with positive Net Present Value.
Keywords: Net present value; Grain terminal; Santos, Brazil; Wheat imports; Internal rate of return; Agriculture, General (0473); Education, Agricultural (0517); Transportation (0709)